The impact of the Affordable Care Act on health insurance coverage in the Gulf Coast and the Rest of the United States by rural and urban areas - Hosik Min; Kenneth Hudson (Journal of Health and Social Sciences)
Introduction: This study examines the effects of the Affordable Care Act (ACA) on rural and urban health insurance coverage in the Gulf Coast region of the United States, which includes five states: Alabama (AL), Florida (FL), Mississippi (MS), Louisiana (LA), and Texas (TX). Methods: Data from the 2009 and 2015 American Community survey micro-sample was used to examine the effects of ACA policy on health insurance coverage in the Gulf Coast states and the rest of the nation. Health insurance coverage rates were presented before and after the implementation of the ACA for rural and urban areas in the Gulf Coast states region and for the rest of the nation. Multivariate logistic regression was used to estimate the likelihood of coverage net of relevant socio-demographic and labor market variables. Results: Our results show the implementation of the ACA increased health insurance coverage nationwide but was still less in the Gulf Coast states than rest of the nation, and less in rural than urban areas. Within the Gulf Coast states region, the increase in coverage varied by state and by rural and urban areas. In Alabama and Mississippi, the net increase in rural areas was 26.2% but in Florida, Texas, and Louisiana, it was only 0.8%. Coverage increased in urban areas in all of the Gulf Coast (28% for AL and MS, 54% in FL, LA, and TX) but less than the rest of the nation (85%). The health insurance coverage for the rural area compared to urban area after the ACA implementation was higher by 17% in Alabama and Mississippi, yet lower by 23% in Florida, Louisiana, and Texas. Discussion and Conclusions: Although the Gulf Coast states did not expand their Medicaid programs, each of the states showed some increase in health insurance coverage after the implementation of the ACA. Future research should examine the health insurance area boundaries on insurance coverage and the effects of the Medicaid Waiver program and in each state.